Fim-de-semana na Aldeia - Projecto para a recuperação de uma casa transmontana - Bruno Filipe Oliveira Vieira Meleiro (2018)
In this dissertation it is presented an architecture project for the refurbishment of a dwelling in a rural context. The weekend house is located in Urrós, Mogadouro, in the Trás-os-Montes region. It is a family dwelling that is empty and unused nowadays and in an initial state of degradation. Both the building's value and the family's memories are recognized and result in the intention of interpreting, retrieving and using it in a future dwelling. Through the structure of the dissertation, it is intended to approach the several moments which took part of the design process, from the first intentions of intervention to the renovation project in its most consolidated phase. The work course presents different moments of development. There are many themes essential to the accomplishment and contextualization of the project: the methodology, the acknowledgment of the site, the memory associated to the existing house, the context in the territory, the morphological transformations of the building and the village and the program are subjects that are addressed throughout this dissertation, interleaved with the presentation of several studies for the project, corresponding to specific moments. Some architectural references are studied, suitable to the problems and solutions found in the project and different design tools are explored. There are progresses and setbacks. The main goal is to establish a proper work methodology appropriate to the exercise of the project design in these circumstances.